Study on the Overseas Communication of Ba-and-Shu Culture in International Chinese Language Education in Universities and Colleges of Sichuan Province: Taking X University as an Example: 四川高校国际汉语教育中巴蜀文化对外传播调查研究 ——以四川省X大学为例 - Xuan ZHANG; Zijing CHENG; Xiaodi GUO (Mandarinable: Journal of Chinese Studies, 2022)
The international spread of Ba-and-Shu Culture (local culture of Sichuan and Chongqing) can promote the soft power of China, especially in Sichuan Province and Chongqing Municipality and their international economic and trade exchanges. With the basis and capacity of cultural research, as well as the channel and capacity of cultural transmission, the universities located in Sichuan and Chongqing should take the task of international communication of Ba-and-Shu Culture. Through interviewing, online questionnaire and data collection, this paper preliminarily studies how X University has studied and transmitted Ba-and-Shu Culture. Problems are identified during the process of research with corresponding measures for optimization, which sets the stage for further study.